the discriminant b^2 - 4ac when the equation is in the form of ax^2 +bx+c=0
13x^2-16x = x^2 -x
we need to get in it the standard form
subtract x^2 from each side
12x^2 -16x = -x
add x to each side
12x^2 -15x = 0
12x^2 -15x -0 =0
a=12 b=-15 c=0
b^2 -4ac
the discriminant = b^2
b^2 = (-15)2 = 225
Answer: 31.11269837 round your answer if needed to
Step-by-step explanation:
Answer:
1/3
Step-by-step explanation:
Answer:
Step-by-step explanation:
In the case of each of the answers listed above, the second derivative is equal to -4 times the function, as required by the differential equation.
For y = 2/3t^3, the second derivative is 4t, not -4y.
For y = e^(2t), the second derivative is 4y, not -4y.
__
The graph shows the sum of the second derivative and 4y is zero for the answers indicated above, and not zero for the other two proposed answers.